Impact of Vaccination on Symptomatology among COVID-19 Infection and Re-infection - Muhammad Kashif Munir, Sana Rehman, Ayesha Aftab, Muhammad Amer Nazir, Akhtar Ali, Naeem Asghar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Present indications proposed strong bases that people suffered from SARS-CoV-2 infection are still susceptible to re-infection. Studies proposed that one of the COVID-19 viral vector vaccine and two genetic mRNA vaccines presented generous defense for COVID-19 infection as well as persisted effectively against mutated variants. Aim: To observe the impact of vaccination symptomatology among patients presented with COVID-19 infection for the first time and compared it with those of re-infected cases during 5th wave in Pakistan Methods: This descriptive study included a total of 248 patients were interviewed using a semi-structured questionnaire. Patients themselves or their attendants receiving reports from the counter of various laboratories were targeted. A verbal informed consent was taken before data collection. Following information about, job nature, side effects after vaccination, comorbidities, level of symptoms (i.e. mild, moderate and high) Results: A total 248 patients consisting of 52.0% females and 48.0% males with overall mean age of 35.96±17.94 years. A total of 37.5% patients were re-infected further proportion of male gender 46.2% and 29.5% were females. Proportion of re-infection in fully vaccinated group remained to be 35.5%, partially vaccinated as 43.9% and unvaccinated as 42.9%. ANOVA was applied to compare the severity of symptoms with full, partial and unvaccinated patients. Conclusion: Lack of discernable variations in protection against COVID-19 re-infection were observe through vaccination or prior infection. Ultimately trends show an enhancement in level of protection from re-infection was shown as prior infection alone, partial vaccination and full vaccination respectively. Keywords: COVID-19, SARS-CoV-2, re-infection, Symptomatology